Original paperThe retina dose-area histogram: a metric for quantitatively comparing rival eye plaque treatment options - Astrahan, Melvin A. (Journal of Contemporary Brachytherapy, 2013)
Purpose: Episcleral plaques have a history of over a half century in the delivery of radiation therapy to intraocular tumors such as choroidal melanoma. Although the tumor control rate is high, vision-impairing complications subsequent to treatment remain an issue. Notable, late complications are radiation retinopathy and maculopathy. The obvious way to reduce the risk of radiation damage to the retina is to conform the prescribed isodose surface to the tumor base and to reduce the dose delivered to the surrounding healthy retina, especially the macula. Using a fusion of fundus photography, ultrasound and CT images, tumor size, shape and location within the eye can be accurately simulated as part of the radiation planning process. In this work an adaptation of the dose-volume histogram (DVH), the retina dose-area histogram (RDAH) is introduced as a metric to help compare rival plaque designs and conformal treatment planning options with the goal of reducing radiation retinopathy. Material and methods: The RDAH is calculated by transforming a digitized fundus-photo collage of the tumor into a rasterized polar map of the retinal surface known as a retinal diagram (RD). The perimeter of the tumor base is digitized on the RD and its area computed. Area and radiation dose are calculated for every pixel in the RD. Results : The areal resolution of the RDAH is a function of the pixel resolution of the raster image used to display the RD and the number of polygon edges used to digitize the perimeter of the tumor base. A practical demonstration is presented. Conclusions : The RDAH provides a quantitative metric by which episcleral plaque treatment plan options may be evaluated and compared in order to confirm adequate dosimetric coverage of the tumor and margin, and to help minimize dose to the macula and retina.